ATP-citrate lyase multimerization is required for coenzyme-A substrate binding and catalysis - Bazilevsky, Gleb A. (J Biol Chem, 2019)
ATP-citrate lyase (ACLY) is a major source of nucleocytosolic acetyl-CoA, a fundamental building block of carbon metabolism in eukaryotes. ACLY is aberrantly regulated in many cancers, cardiovascular disease, and metabolic disorders. However, the molecular mechanisms determining ACLY activity and function are unclear. To this end, we investigated the role of the uncharacterized ACLY C-terminal citrate synthase homology domain in the mechanism of acetyl-CoA formation. Using recombinant, purified ACLY and a suite of biochemical and biophysical approaches, including analytical ultracentrifugation, dynamic light scattering, and thermal stability assays, we demonstrated that the C terminus maintains ACLY tetramerization, a conserved and essential quaternary structure in vitro and likely also in vivo. Furthermore, we show that the C terminus, only in the context of the full-length enzyme, is necessary for full ACLY binding to CoA. Together, we demonstrate that ACLY forms a homotetramer through the C terminus to facilitate CoA binding and acetyl-CoA production. Our findings highlight a novel and unique role of the C-terminal citrate synthase homology domain in ACLY function and catalysis, adding to the understanding of the molecular basis for acetyl-CoA synthesis by ACLY. This newly discovered means of ACLY regulation has implications for the development of novel ACLY modulators to target acetyl-CoA–dependent cellular processes for potential therapeutic use.